Cotas raciais como reconhecimento na teoria da justiça de Axel Honneth - Thiago Aguiar Simim (2014)
The starting point of this dissertation takes is the debate carried around the (in)justice of the racial quotas to access public university in Brazil. In the juridical realm, the work analyzes the discourse of the Claim of Breach of Fundamental Precept (ADPF - Arguição de Descumprimento de Preceito Fundamental) nº 186, raised against the racial quotas implemented at the University of Brasília (UNB), which gained importance in the debate in the local public sphere. The core arguments of this debate are based in thesis of the liberal theory of justice and in a biased lecture of the history of Brazil concerning racial relations and social classes. This works resorts to the debate of Axel Honneth in the field of the theories of justice and to his own proposition of a theory of recognition as a theory of justice, which faces the criticism of its distance from social reality. The second chapter, which intends to elucidate Honneths theory, turns to the hegelian philosophical basis in defense of a formal concept of ethical life which permits that historically embedded patterns of recognition provide the personal self-realization of individuals that involves social integration generated through the process of individualization and socialization. In a second moment, Honneth leaves the analysis focused in the social conflict, and he enlarges the normative basis of his theory with the reconstruction of the social institutions in which social freedom is turned effective. At this point, Honneth aims to pursue the critical goals of the Frankfurt School, namely, to produce diagnosis of time anchored in the praxis and oriented to human emancipation, from the disclosure of social pathologies. Thus, his diagnosis is normative and it offers the basis to think those principles of justice embedded in the social institutions. The third and last part of the work analyzes questions of race and class in post-slavery Brazil in a critical confrontation to the tradition of the interpreters of Brazil, so that it becomes possible to turn back to the current debate about racial or social quotas. From this point, the work outlines the basis of an empirical research which would be able to produce a diagnosis of the analyzed social pathologies, like the covert racism and the ideology of merit, at the same time as it confronts the investigation of individual self-realization provided by racial quotas. As a conclusion, the work discusses the limits of the racial quotas as a reflex of the limits of the juridical sphere itself and the possibilities of irradiation of racial quotas to other historically interconnected social realms, like work and social class.